Answer:
The volume of cylinder and the volume of a cone, have equal volume measurements. So, the answer is C).
Step-by-step explanation:
Cylinder:
-Use the formula for the volume of a cylinder. Use both the radius and height for the formula in order to solve and get the volume:
![V = \pi r^2 h](https://tex.z-dn.net/?f=V%20%3D%20%5Cpi%20r%5E2%20h)
![V = \pi 2^2 6](https://tex.z-dn.net/?f=V%20%3D%20%5Cpi%202%5E2%206)
-Solve:
![V = \pi 2^2 6](https://tex.z-dn.net/?f=V%20%3D%20%5Cpi%202%5E2%206)
![V = \pi \times 2^2 \times 6](https://tex.z-dn.net/?f=V%20%3D%20%5Cpi%20%5Ctimes%202%5E2%20%5Ctimes%206)
![V = \pi \times 4 \times 6](https://tex.z-dn.net/?f=V%20%3D%20%5Cpi%20%5Ctimes%204%20%5Ctimes%206)
![V = \pi \times 24](https://tex.z-dn.net/?f=V%20%3D%20%5Cpi%20%5Ctimes%2024)
--------------------------------------------------------------------------------------------------------
Cone:
-Use the formula for the volume of a cone and the radius and height for the formula and solve the formula to get the volume:
![V = \frac{1}{3} \pi r^2h](https://tex.z-dn.net/?f=V%20%3D%20%5Cfrac%7B1%7D%7B3%7D%20%5Cpi%20r%5E2h)
![V = \frac{1}{3} \pi 3^28](https://tex.z-dn.net/?f=V%20%3D%20%5Cfrac%7B1%7D%7B3%7D%20%5Cpi%203%5E28)
-Solve:
![V = \frac{1}{3} \pi 3^28](https://tex.z-dn.net/?f=V%20%3D%20%5Cfrac%7B1%7D%7B3%7D%20%5Cpi%203%5E28)
![V = \frac{1}{3} \times \pi \times 3^2 \times 8](https://tex.z-dn.net/?f=V%20%3D%20%5Cfrac%7B1%7D%7B3%7D%20%5Ctimes%20%5Cpi%20%5Ctimes%203%5E2%20%5Ctimes%208)
![V = \frac{1}{3} \times \pi \times 9 \times 8](https://tex.z-dn.net/?f=V%20%3D%20%5Cfrac%7B1%7D%7B3%7D%20%5Ctimes%20%5Cpi%20%5Ctimes%209%20%5Ctimes%208)
![V = \frac{1}{3} \times \pi \times 72](https://tex.z-dn.net/?f=V%20%3D%20%5Cfrac%7B1%7D%7B3%7D%20%5Ctimes%20%5Cpi%20%5Ctimes%2072)
![V = \frac{1}{3} \pi \times 72](https://tex.z-dn.net/?f=V%20%3D%20%5Cfrac%7B1%7D%7B3%7D%20%5Cpi%20%5Ctimes%2072)
-So, according to the volume of a cylinder and the volume of a cone, They both have the same volume.
Cylinder:
![ft^3](https://tex.z-dn.net/?f=ft%5E3)
Cone:
![ft^3](https://tex.z-dn.net/?f=ft%5E3)
Step-by-step explanation:
i think a is the answer of this question.
10•4=40. 40 is the perimeter of the square. To find the perimeter of the semicircle use the circle perimeter (circumference) formula and divide that answer by two. This would be pi•10. You get 31.4. Then divide by 2 so it’s 15.7. Finally add 15.7 and 40. Hope this helps... sorry it’s such a long answer
Answer:
Unknown answer so ye that mean I'm not sure about it
Step-by-step explanation:
Unknown answer so ye that mean I'm not sure about it
Answer with Step-by-step explanation:
We are given that a function
![f(x)=x^3-x^2-17x-15](https://tex.z-dn.net/?f=f%28x%29%3Dx%5E3-x%5E2-17x-15)
We have to find the graph of the given function.
y-intercept:It is that value of y where the graph cut the y- axis.
Let
![y=f(x)=x^3-x^2-17x-15](https://tex.z-dn.net/?f=y%3Df%28x%29%3Dx%5E3-x%5E2-17x-15)
Substitute x=0
Then, we get
![f(0)=-15](https://tex.z-dn.net/?f=f%280%29%3D-15)
y-intercept of the graph=-15
x- intercept: It is that value of x where the graph cut the x- axis.
Substitute y=0
![x^3-x^2-17x-15=0](https://tex.z-dn.net/?f=x%5E3-x%5E2-17x-15%3D0)
Substitute x=-1
![-1-1+17-15=0](https://tex.z-dn.net/?f=-1-1%2B17-15%3D0)
Therefore,x=-1 is a solution of given equation.
![(x+1)(x^2-2x-15)=0](https://tex.z-dn.net/?f=%28x%2B1%29%28x%5E2-2x-15%29%3D0)
![(x+1)(x^2-5x+3x-15)=0](https://tex.z-dn.net/?f=%28x%2B1%29%28x%5E2-5x%2B3x-15%29%3D0)
![(x+1)(x(x-5)+3(x-5))=0](https://tex.z-dn.net/?f=%28x%2B1%29%28x%28x-5%29%2B3%28x-5%29%29%3D0)
![(x+1)(x+3)(x-5)=0](https://tex.z-dn.net/?f=%28x%2B1%29%28x%2B3%29%28x-5%29%3D0)
![\implies x=-1,-3,5](https://tex.z-dn.net/?f=%5Cimplies%20x%3D-1%2C-3%2C5)
Hence, the x-intercept are
-3,-1 and 5